Blocked But Not Tackled - Carnahan, Seth (Strategic Management Journal, 2017)
[Research summary: This article examines the role of competitive shocks in creating opportunities for new firm foundings. I argue that the sudden dissolution of rival firms may release resources that create opportunities for firm formation, particularly among employees facing impediments to capturing value in their current organizations. Analyzing microdata from the legal services industry, I use unexpected deaths of solo-practicing attorneys as quasi-exogenous sources of rival dissolution. Results indicate that these shocks increase the odds of founding by about 30%, with stronger effects among attorneys with weaker social connections or higher competition for promotion. The article thus highlights the role that founders play in reallocating dissolved rivals’ resources while demonstrating that founding may be an important outlet for “blocked” employees to capture value from opportunities. Managerial summary:This article finds that the shutdown and dissolution of a rival organization may spur employees to found new firms. As a consequence, managers may find it valuable to pay attention to employees’ turnover intentions following the dissolution of a rival. Findings suggest that employees who are having trouble advancing in the firm may be the most likely to found a new organization when a rival dissolves, so managers may want to focus retention efforts on these individuals. To the extent that managers wish to capture customers, employees, and other resources that were formerly attached to a dissolved rival, managers may wish to be aware that they could be in competition with their own employees for these resources and opportunities.]